The neural network behind the eyes of a fly. Issue 16 (August 2020) - Borst, Alexander; Drews, Michael; Meier, Matthias
Abstract : With its regular, almost crystal-like structure, the fly optic lobe represents a particularly beautiful piece of nervous system, which consequently has attracted the attention of many researchers over the years. While the anatomy of the various cell types had been known from Golgi studies for long, their visual response properties could only recently be revealed thanks to the advent of cell-specific driver lines and genetically encoded indicators of neural activity. Furthermore, dense EM reconstruction of several columns of the fly optic lobe now provides information about the synaptic connections between the different cell types, and RNA sequencing sheds light on the transmitter systems and ionic conductances used for communication between them. Together with the molecular tools allowing for blocking and activating individual, genetically targeted cell types, the fly optic lobe can soon be one of the best-understood visual neuropils in neuroscience. In this review, we summarize what we have learned so far, and discuss the major difficulties that keep us from a complete understanding of visual processing in the fly optic lobe.